Past, Present and Future of Assistive Robotic Lower Limb Exoskeletons - Narina Ramesh; Iwaniec Marek; Arawade Swapnil (MATEC Web of Conferences, 2022)
Many research teams have developed various innovations in the field of assistive robotic exoskeletons for human lower limbs. Especially in the recent years, because of the expeditious technological development, much work has been done and published in the scientific communities. However, in the publications, for different reasons and constraints, the information available is in bits and pieces. Most papers only could manage to speak of the individual aspects like the mechanical design or state machine or interface or another control scenario, etc. This is why an attempt of bringing scientific aspects together is done in this work. This is achieved by considering the most popular and various kinds of exoskeletons. Therefore, in this chapter an overview on the aspects of mechanical design and electrical control, and simultaneously their algorithms were discussed. Coming to analytical simulations like forward and inverse kinematics, dynamic simulation of the moments of the multibody system, etc., were performed in ADAMS and OpenSim simulation platforms. Better solutions were proposed and awaiting challenges were discussed for each aspect of the robotic exoskeleton.